Administration of anticonvulsive rescue medication in children: discrepancies between parents’ self-reports and limited practical performance - Kaune, Almuth; Syrbe, Steffen (European journal of pediatrics, 2016)
Quality of parents’ performance in administering anticonvulsive rescue medication to their children suffering from seizures is unknown. After obtaining ethical approval, we used a questionnaire to ask parents of children with seizures, who had been prescribed rescue medications, about their experience in administering those. To assess the frequency of actually committed drug-handling errors, we let them administer rescue medications to dummy dolls. An expert panel rated the clinical risk of handling errors from “1” (lowest) to “6” (highest). Eighty-one parents completed the study. In the questionnaire, 85 % (100 %) of parents that already conducted rectal (buccal) administration reported that they had never experienced problems. The number of rectal administrations with at least one handling error (97 %, 58/60) was higher than in buccal administration (58 %; 14/24; p < 0.001). According to logistic regressions, previous use of rescue medication was not a predictor of the number of committed errors per process (n. s.). All errors were rated with a high clinical risk (class 4-6). Conclusion: By observing parents’ administration of rescue medication to dummy dolls, we found a high frequency of clinically relevant drug-handling errors. Most parents, however, self-reported to have never experienced problems while administering rescue medications to their children. What is Known: • For seizures with duration of more than 5 min, the administration of anticonvulsive rescue medication is recommended. • Outside the hospital, the administration of rescue medication to children is performed most frequently by their parents. What is New: • Most of the parents reported that they had never experienced problems in handling anticonvulsive rescue medication. • But in the observed drug-handling performances, identified errors committed by parents were alarmingly frequent and pose a high clinical risk according to an expert panel.